Legal Protection For Debtors In Selling Of Immovable Guaranteed Objects Below The Market Price In Indonesian Positive Law - Dyatmika Malik; Mangirim Limbong; Sri Endah Wahyuningsih (Jurnal Akta, 2018)
The difference price that occurs, in the implementation of execution of the debtor’s collateral object, the creditor should pay attention on the debtor’s right, ie the debtor should get a normal price on the guaranteed good which is being executed. It is related to the debtor's obligation, in case that the object’s price is under the value of the debt. The issues raised in this study are how the process of selling immovable goods under the positive law in Indonesia, How the actions that can be done by the debtor if the guaranty is sold by the creditor below the market price, How legal protection for the debtor in selling the immovable goods under the provisions of Indonesia's positive law. The research method used was normative juridical research with approach of law, concept, and case study. The results of this study found that, first, the initial procedure in selling the immovable goods is through an auction request. The auction request is made by the seller, in this case the creditor. Second, if the sale is conducted through auction, it can be requested for loss of a lawsuit against the law only found any mistake in the implementation of auction procedures. And third, these aspects include: Debtor position related to the determination of the limit value, the position of the debtor in the event of auction cancellation; The position of the debtor in the case of the sale of a guaranteed underhand object; and the position of the debtor when the item has been sold and is in a third party.Keywords: Protection; Sale; Positive Law; Immovable Objects